HUBUNGAN ANTARA ASUPAN SERAT DAN ASUPAN AIR PUTIH DENGAN KEJADIAN KONSTIPASI PADA LANSIA - joko pitoyo; Khabiba Puswita Sari (Jurnal Keperawatan Terapan, 2019)
Constipation becomes one of the diseases which is often suffered by elderly. Lack of fiber intake and water intake are some of the factors that influence the occurrence of constipation. The purpose of the study was to know the correlation between fiber intake and water intake with constipation occurrence in elderly in RW 18 Kelurahan Bunul Rejo Blimbing District Malang. The type of the study was analytical survey with cross sectional approach. The number of sample were 68 people, the samples were taken with purposive sampling technique, and the data were collected by using food recall and constipation scoring system questionnaire. Based on the result of fiber intake, it is obtained p value is 0.000 with r is 0.444 and for water intake it is gotten p value is 0,000 with r is 0.838. it shows there is a correlation between fiber intake and water intake with constipation occurrence in elderly in RW 18 Kelurahan Bunul Rejo Blimbing District of Malang city. From the above result, the health education about the importance of fiber intake and water intake is required to prevent constipation in elderly.